2008
DOI: 10.1634/stemcells.2008-0311
|View full text |Cite
|
Sign up to set email alerts
|

A Developmentally Regulated Heparan Sulfate Epitope Defines a Subpopulation with Increased Blood Potential During Mesodermal Differentiation

Abstract: Heparan sulfate (HS) is a mandatory coreceptor for many growth factors and morphogens involved in embryonic de STEM CELLS 2008;26:3108 -3118 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…Ndst1/2 null ESCs, which are devoid of N-sulfation and 2-O-sulfation, fail to differentiate into endothelial cells (19,25). ESCs deficient in Ext1 do not produce any HS and could not be induced to differentiate into neuronal cell types (21). These studies illustrate that HS is essential for ESC differentiation into multiple cell lineages.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Ndst1/2 null ESCs, which are devoid of N-sulfation and 2-O-sulfation, fail to differentiate into endothelial cells (19,25). ESCs deficient in Ext1 do not produce any HS and could not be induced to differentiate into neuronal cell types (21). These studies illustrate that HS is essential for ESC differentiation into multiple cell lineages.…”
mentioning
confidence: 78%
“…Recent reports have demonstrated that the HS structure changes as ESCs undergo differentiation and that specific HS epitopes appear on subpopulations of differentiated ESCs, suggesting that HS regulates ESC differentiation and cell lineage development (21,22,24). This presumption has been supported by the examination of ESCs lacking Ndst1/2 (N-deacetylase/N-sulfotransferase 1/2) or Ext1.…”
mentioning
confidence: 92%
“…Matched 129Sv wild-type ESCs were generated in house. ESCs were maintained on irradiated feeder cells, and transferred to gelatin for two passages prior to EB generation as described previously (19). Recombinant mouse Noggin/Fc chimera (0.2 g/ml, R&D systems, Abingdon, UK) and SB431542 (10 M, Tocris, Bristol, UK) were dissolved in DMSO and added at day 0 alongside a DMSO alone control.…”
Section: Esc Maintenance and Eb Differentiation-ext1mentioning
confidence: 99%
“…2 g of total RNA was reverse-transcribed into cDNA using oligo-dT and AMV reverse transcriptase (Promega, Southampton, UK). PCR was performed as described previously (19). For primer sequences see supplemental Table S1.…”
Section: Esc Maintenance and Eb Differentiation-ext1mentioning
confidence: 99%
“…Early studies of primary neural cells and differentiated teratocarcinoma cells demonstrated rapid alteration in HS sulfation patterns and core protein expression concomitant with temporal expression of FGFs [18][19][20]. Now HSPGs are well recognized as important modulators of growth factor signaling and morphogen gradients across a range of developmental processes [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%